2018
DOI: 10.1111/are.13656
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary levels of protein on growth, feed utilization and physiological parameters for juvenile Dabry's sturgeon,Acipenser dabryanus

Abstract: Five semi-purified diets were formulated to contain graded levels of dietary protein (340, 390, 440, 490 and 540 g/kg diet), and each diet was assigned to triplicate groups of eight juvenile Dabry's sturgeon for 50 days. Results showed that specific growth rate increased linearly with increasing dietary protein levels from 340 to 440 g/kg diet, then levelled off at higher protein levels. Higher dietary protein (440 and 540 g/kg) significantly increased the feed intake and feed efficiency ratio of fish compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The results of this study showed that the 100% survival of C. mongolicus fingerlings, indicating an adaptation to a wide range of dietary protein levels. These findings are similar to these of previous studies on Brazilian sardine [8], Rhamdia quelen [13], Nibea diacanthus juveniles [17], Dabry's sturgeon juveniles [54], bluegill sunfish juveniles [55], and juvenile marbled spinefoot rabbit fish [56]. These results suggest that dietary protein levels may not be a determinant factor of the mortality.…”
Section: Growth Performancesupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this study showed that the 100% survival of C. mongolicus fingerlings, indicating an adaptation to a wide range of dietary protein levels. These findings are similar to these of previous studies on Brazilian sardine [8], Rhamdia quelen [13], Nibea diacanthus juveniles [17], Dabry's sturgeon juveniles [54], bluegill sunfish juveniles [55], and juvenile marbled spinefoot rabbit fish [56]. These results suggest that dietary protein levels may not be a determinant factor of the mortality.…”
Section: Growth Performancesupporting
confidence: 90%
“…All data were subjected to one-way analysis of variance (ANOVA) using SPSS 22.0 (SPSS, IL, USA), after checking for the normality and homogeneity, followed by Duncan's multiple comparison analysis to conduct pairwise comparisons. The optimum dietary protein requirement based on the total length and weight-specific growth rate was estimated using broken-line regression analysis (y = L − U × (R − x), y means specific growth rate, x means protein content) [17,54] in Excel 2016. The data were expressed as mean ± SE (standard error).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much effort has been carried out to support the recovery of this endangered species, including the legislation of fishing ban, construction of natural reserve, controlled reproduction and restocking of cultured juveniles (Fan et al, 2006; Zhang et al, 2011). In particular, artificial propagation and release have been recommended as an effective approach to recruit wild populations (Li et al, 2018). However, the immature technology of large‐scale seedling cultivation of Dabry's sturgeon results in a small number of fish that can be released and a low speed of establishment of the artificial population echelon, which limits the scale of release and increases the difficulties in their protection.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, Acipenser dabryanus are nowadays commonly fed on commercial pellets designed for farmed sturgeon species, for example, hybrid sturgeon. Our previous study has determined the optimum dietary protein level for the Yangtze sturgeon with reported values of 44.6% for juveniles up to 300 g (Li et al, 2018). As with protein, the lipid is another important macronutrient in the diet, which provides essential fatty acids, phospholipids, sterols, fat‐soluble vitamins and carotenoids for maintaining not only rapid somatic growth but also normal cell structure and function (Opstvedt, 1997).…”
Section: Introductionmentioning
confidence: 99%